The association between polypharmacy, frailty and disability-free survival in community-dwelling healthy older individuals. (July 2022) - Ekram, A R M Saifuddin; Woods, Robyn L.; Ryan, Joanne; Espinoza, Sara E.; Gilmartin-Thomas, Julia F.M.; Shah, Raj C.; Mehta, Raaj; Kochar, Bharati; Lowthian, Judy A.; Lockery, Jessica; Orchard, Suzanne; Nelson, Mark; et al.
Highlights: Polypharmacy and frailty are two common geriatric conditions. Polypharmacy is significantly associated with pre-frailty and frailty. Polypharmacy-exposed frailty increases the risk of reduced disability-free survival. Addressing polypharmacy could ameliorate the impact of frailty on disability-free survival. Abstract: Objectives: Polypharmacy and frailty are two common geriatric conditions. In community-dwelling healthy older adults, we examined whether polypharmacy is associated with frailty and affects disability-free survival (DFS), assessed as a composite of death, dementia, or persistent physical disability. Methods: We included 19, 114 participants (median age 74.0 years, IQR: 6.1 years) from ASPirin in Reducing Events in the Elderly (ASPREE) clinical trial. Frailty was assessed by a modified Fried phenotype and a deficit accumulation Frailty Index (FI). Polypharmacy was defined as concomitant use of five or more prescription medications. Multinomial logistic regression was used to examine the cross-sectional association between polypharmacy and frailty at base line, and Cox regression to determine the effect of polypharmacy and frailty on DFS over five years. Results: Individuals with polypharmacy (vs. <5 medications) were 55% more likely to be pre-frail (Relative Risk Ratio or RRR: 1.55; 95%Confidence Interval or CI:1.44, 1.68) and three times more likely to be frail (RRR: 3.34; 95%CI:2.64, 4.22) according to Fried phenotype. Frailty alone was associated with double risk of the composite outcome (Hazard ratio or HR: 2.16; 95%CI: 1.56, 2.99), but frail individuals using polypharmacy had a four-fold risk (HR: 4.24; 95%CI: 3.28, 5.47). Effect sizes were larger when frailty was assessed using the FI. Conclusion: Polypharmacy was significantly associated with pre-frailty and frailty at baseline. Polypharmacy-exposed frailty increased the risk of reducing disability-free survival among older adults. Addressing polypharmacy in older people could ameliorate the impact of frailty on individuals' functional status, cognition and survival. Graphical abstract: Image, graphical abstract